Pergeseran Fungsi Tradisi Hombo Batu pada Masyarakat Nias Selatan - Indah Wijaya Lase; Junaidi Indrawadi; Maria Montessori (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
This article aims to describe the shift in the function of the Hombo Batu tradition in the people of Nias Selatan. The problem in this research is focused on the shape of the shift in the function of the Hombo Batu tradition and the factors that cause the shift in the Hombo Batu tradition. This research uses a descriptive qualitative approach. Data collection techniques are observation, interview and documentation. Testing the validity of the data using triangulation techniques.Data analysis techniques with data reduction, data presentation, and drawing conclusions / verification. The results of the study found that there had been a shift in the function of the Hombo Batu tradition from a physical training function for war to become a tourism icon. The factors causing the shift are internal factors and external factors. This study concludes that there has been a shift in the function of the Hombo Batu tradition with its internal factors concerning the growing idea of the people of South Nias making the Hombo Batu tradition a tourist icon with its income and commercial. External factors were found in the arrival of German missionaries, the entry and advancement of national education, and the presence of tourists.